2019
DOI: 10.1177/0963689719861922
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates of Various Autologous Chondrocyte Grafts and Concomitant Procedures. A Prospective Single-Center Study over 18 Years

Abstract: Seven different autologous chondrocyte implantation (ACI) grafts were used consecutively over a period of 18 years for the treatment of cartilage lesions in the knees. The aim was to evaluate this entire ACI patient series for graft-related or unrelated serious adverse events (SAE), graft failures, and to reveal potential risk factors for these incidents. The study group comprised 151 operated patients: classical periosteum-ACI (n = 45); ACI-seeded fibrin-collagen patch, fixed by either periosteum (n = 59), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…In fact, different failure rates were documented in this series, with female patients and patients affected by degenerative lesions being more at risk. This confirms previous literature 13,14,21 supporting the negative influence of a degenerative joint environment on the survival of MACT, 3,8 as well as the poorer outcome often documented in women. This is a controversial aspect.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, different failure rates were documented in this series, with female patients and patients affected by degenerative lesions being more at risk. This confirms previous literature 13,14,21 supporting the negative influence of a degenerative joint environment on the survival of MACT, 3,8 as well as the poorer outcome often documented in women. This is a controversial aspect.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies have documented overall good findings for these regenerative strategies to address lesions of the articular surface, and after >20 years from their introduction in clinical practice, long-term reports about first-generation ACI are being published, documenting durability of the results. 6,21,26,30 Several studies have presented data with >12 years of follow-up, reporting long-lasting clinical improvement, with a failure rate ranging from 25% to 37% at long-term follow-up. 6,24,26 Long-term evaluation is particularly important for these treatments, since patients undergoing surgery are often young and focused on recovering and maintaining an active lifestyle.…”
mentioning
confidence: 99%
“…Ogura et al 27 demonstrated this phenomenon in a study on revision ACI in which their analysis demonstrated failure rates of 30% to 50% at 5-and 10-year follow-up for revision ACI, which is inferior to that seen in primary ACI. 2,5,19 This has also been seen for other cartilage procedures in the knee, such as osteochondral allograft. 14 Given that ACI after a prior BMS represents a revision scenario, it is not surprising that the results of this paper demonstrated a similar trend to other revision cartilage restoration techniques, which suggests that a revision setting alone may contribute to increased failure rates.…”
Section: Discussionmentioning
confidence: 78%
“…Patient-specific factors include increased age, female sex, and WC status. 19,30,33 Lesion-specific factors include complexity of lesion, history of prior surgeries of the affected joint, first-generation ACI technique, lesion size >4.5 cm 2 , and the failure to perform concomitant tibial tubercle osteotomy when indicated. 15,21,28,30 These risk factors have been described elsewhere in the literature, and given the heterogeneity of data reporting in the included studies, we could not adjust for all these factors in our review.…”
Section: Discussionmentioning
confidence: 99%
“…However, most patients (70% of cases) have combined lesions, or "red knees" [17,18]. Martinčič et al [19] followed 151 patients for an average of 10 years after knee cartilage repair. They found no statistically signi cant difference in outcomes between patients with and without a history of prior surgery.…”
Section: Discussionmentioning
confidence: 99%